E-Market Place Application "Computer Devices" in the City of Medan - Fermadi, Fermadi; Kurniawan, Helmi (Jurnal Manajemen, Informatika, Rekayasa Perangkat Lunak dan Teknologi Komunikasi, 2023)
A computer device is all the physical parts of a computer, and is distinguished by the data that is in it or that operates on it, and is distinguished from software that provides instructions for the hardware in completing its tasks. So far, marketing is still constrained in terms of promotion and marketing of computer peripheral products. so that buyers still do not know what products are sold by a particular company or shop. Several shops and companies in the city of Medan also face problems in terms of the details of orders by buyers and ordering computer hardware products using only the telephone or face to face. Goods data collection is still conventional, namely by entering the data into a price list book, sales transaction book and so on. So that conducting transactions and entering data must open the sales transaction data book. In this study, the authors raised several companies engaged in the computer equipment business. And another obstacle is that sellers often experience problems in carrying out the process of promoting and selling computer equipment that has been ordered by customers. The process of submitting cooperation between sellers and suppliers is still done manually. The process of selling computer equipment to companies is done by Via Call.